Digital technologies in teaching Russian as a foreign language - Genjebaeva, Zarafshan Salamatovna (The Lingua Spectrum, 2026)
The article examines the features of the use of digital technologies in teaching Russian as a foreign language (RFL) in the context of the active digitalization of the modern educational space. The key directions of the introduction of information and communication technologies in the process of teaching foreign students the Russian language are analyzed, as well as the pedagogical possibilities of the digital educational environment in the context of the formation of language, speech and communicative competencies of students. Special attention is paid to the use of online platforms, multimedia resources, interactive services, mobile applications and artificial intelligence technologies as effective means of increasing motivation, individualizing learning and developing independent cognitive activity of students. The paper reveals the didactic advantages of digital technologies, among which are the availability of educational materials, the flexibility of the educational process, the possibility of modeling communicative situations and operational control of knowledge. Along with this, certain difficulties are considered related to the lack of digital competence of teachers and students, the problems of adapting electronic resources to the goals of RFL training, as well as the risks of reducing the level of live speech interaction. Based on the analysis of scientific works of domestic and foreign researchers, the necessity of integrating digital technologies into modern teaching methods of Russian language is substantiated as an important condition for improving the effectiveness and quality of language education.